Encapsulation of carotenoids with sucrose by co-crystallization: Physicochemical properties, characterization and thermal stability of pigments. (April 2021) - Kaur, Prabhjot; Elsayed, Abdallah; Subramanian, Jayasankar; Singh, Ashutosh
Abstract: Natural pigment carotenoids specifically β-carotene present in carrots is very sensitive to heat and light. The present work studied the co-crystallization as a process to increase the stability of the carotenoids extracted from carrots. Carotenoids encapsulated co-crystals were evaluated for their encapsulation efficiency, antioxidant activity, thermal behavior, physicochemical, and structural properties. Co-crystallization of the carotenoids with sucrose showed an encapsulation efficiency of 77.58% and an antioxidant activity of 68% towards DPPH free radicals. DSC thermogram confirmed the thermal stability of carotenoids encapsulated co-crystals by indicating the endothermic peaks at 190 °C. XRD pattern and FTIR spectra revealed that the crystal nature of sucrose and functional groups remained the same even after co-crystallization. SEM results revealed the irregular cavities in well-defined cubic crystals of sucrose which suggested the better entrapment of carotenoids into sucrose. Hence, co-crystallization significantly improved the overall stability of the carotenoids, and these co-crystals can be used as a natural colorant, sweetener, and antioxidant. Graphical abstract: Image 1 Highlights: Carotenoid rich extract from the rejected carrots was co-crystalized with sucrose. Co-crystallization of β-carotene resulted in an encapsulation efficiency of 78%. DSC, XRD, and SEM revealed that co-crystals formed are pure crystalline in nature. β-carotene encapsulated co-crystals can be used as a colorant, sweetener, and antioxidant.